An observational study of the macro‐ and micro‐haemodynamic implications of epidural anaesthesia in children. (28th November 2016) - Triffterer, L.; Marhofer, P.; Lechner, G.; Marksz, T. C.; Kimberger, O.; Schmid, W.; Marhofer, D.
Summary: The haemodynamic implications of epidural anaesthesia in children are poorly documented. We report macro‐ and micro‐haemodynamic data from an observational study of 25 children ranging from neonates to six‐years old, who underwent surgery conducted with a specific combination of monitoring systems. We analysed 90 min of study‐related monitoring after epidural catheterisation, with skin incision taking place after around 30 min. We recorded macrohaemodynamic parameters (monitored using LiDCO rapid ) including heart rate, mean arterial pressure, cardiac output, stroke volume, systemic vascular resistance and stroke volume variation. Microhaemodynamic parameters (monitored using Invos™) included cerebral and peri‐renal oxygenation. Based on the entire 90 min of study‐related monitoring, we found significant increases in cardiac output (p = 0.009), stroke volume (p = 0.006) and stroke volume variation (p = 0.008), as well as decreases in systemic vascular resistance (p = 0.007) around 30 min after epidural blockade. There were no significant changes in heart rate, arterial pressure and cerebral or peri‐renal oxygenation during these 90 min. Considering that the microhaemodynamic parameters were not affected by the macrohaemodynamic changes, we conclude that autoregulation of the brain and the kidneys was maintained in children under epidural anaesthesia.